Noise Pollution in Dental Education: Health Risks and Mitigation Strategies - AMINE, Meriem; BOUALAM, Ayoub; JALIL, Zineb AL (New Ideas Concerning Arts and Social Studies Vol. 2, 2025)
Dental professionals are exposed to various occupational hazards, including noise pollution caused by dental instruments, particularly high-speed handpieces. Since their introduction in the late 1950s, concerns have been raised about their impact on auditory health, as prolonged exposure to high noise levels can lead to both auditory effects (such as hearing impairment, tinnitus, and acoustic trauma) and extra-auditory effects (including stress, cardiovascular issues, cognitive impairment, sleep disturbances, and risks during pregnancy). The acoustic environment in dental education is especially affected due to the simultaneous use of multiple devices, with studies showing noise levels in preclinical training rooms ranging from 69 dB to 81 dB—close to or exceeding the 80 dB threshold set by international standards for preventive action. Factors such as noise intensity, frequency, exposure duration, and individual susceptibility influence the degree of risk. To mitigate these effects, it is essential to implement noise reduction strategies at three levels: at the source (using quieter, well-maintained equipment and limiting unnecessary noise), during propagation (with acoustic treatments like absorbent materials and soundproof barriers), and through individual protection (including earplugs, noise-canceling headphones, and regular audiometric tests). Additionally, using sound level meters to monitor exposure and integrating haptic simulators for silent learning are recommended approaches to improve acoustic comfort and ensure a safer, healthier educational environment in dental schools.